2015
DOI: 10.1161/jaha.115.001777
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Outflow Tract Septal Pacing Is Superior to Right Ventricular Apical Pacing

Abstract: BackgroundThe effects of right ventricular apical pacing (RVAP) and right ventricular outflow tract (RVOT) septal pacing on atrial and ventricular electrophysiology have not been thoroughly compared.Methods and ResultsTo identify a more favorable pacing strategy with fewer adverse effects, 80 patients who had complete atrioventricular block with normal cardiac function and who were treated with either RVAP (n=42) or RVOT septal pacing (n=38) were recruited after an average of 2 years of follow‐up. The data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…One of such studies showed that septal pacing not only did not correlate with LVEF worsening, but also had fewer atrial arrhythmias during the follow-up period [ 11 ] . It should be noted, however, that those patients had a lower percentage of RV pacing when compared to subjects in our study (50-60% vs. > 80%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of such studies showed that septal pacing not only did not correlate with LVEF worsening, but also had fewer atrial arrhythmias during the follow-up period [ 11 ] . It should be noted, however, that those patients had a lower percentage of RV pacing when compared to subjects in our study (50-60% vs. > 80%).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical consequence of such changes manifest through worsening of left ventricular ejection fraction (LVEF) and, in some cases, heart failure (HF) symptoms. Once LVEF starts to fall, it leads to deterioration in quality of life, to an increase in atrial fibrillation burden and to a tendency to a higher mortality [ 7 - 11 ] . The DAVID trial [ 12 ] showed that RV pacing is poorly tolerated by patients and may cause heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…22 Zou et al assessed RVOT septal pacing in their retrospective analysis of 80 patients with complete AV block and normal cardiac function. 2 Patients who received either RVA pacing (n = 42) or RVOT septal pacing (n = 38) were included. 2 During two years of follow-up, six patients developed incident AF in the RVA pacing group, while only one patient with new-onset AF was observed in the RVOT septal pacing group.…”
Section: Studies Evaluating Right Ventricular Outflow Tract and Rightmentioning
confidence: 99%
“…2 Patients who received either RVA pacing (n = 42) or RVOT septal pacing (n = 38) were included. 2 During two years of follow-up, six patients developed incident AF in the RVA pacing group, while only one patient with new-onset AF was observed in the RVOT septal pacing group. Additionally, RVOT septal pacing resulted in a shorter QRS duration, intraventricular mechanical delay, and less left atrial volume increase as compared with RVA pacing.…”
Section: Studies Evaluating Right Ventricular Outflow Tract and Rightmentioning
confidence: 99%
See 1 more Smart Citation